Diffusion of brain metabolites highlights altered brain microstructure in type C hepatic encephalopathy: a 9.4 T preliminary study - Mosso, Jessie; Briand, Guillaume; Pierzchala, Katarzyna; Simicic, Dunja; Sierra, Alejandra; Abdollahzadeh, Ali; Jelescu, Ileana O.; Cudalbu, Cristina (Frontiers in Neuroscience, 2024)
Type C hepatic encephalopathy (HE) is a decompensating event of chronic liver disease leading to severe motor and cognitive impairment. The progression of type C HE is associated with changes in brain metabolite concentrations measured by 1H magnetic resonance spectroscopy (MRS), most noticeably a strong increase in glutamine to detoxify brain ammonia. In addition, alterations of brain cellular architecture have been measured ex-vivo by histology in a rat model of type C HE. The aim of this work was to assess the potential of diffusion-weighted MRS (dMRS) at probing these cellular shape alterations in-vivo by monitoring the diffusion properties of the major brain metabolites. The bile-duct-ligated (BDL) rat model of type C HE was used. Five animals were scanned before surgery and six to seven weeks post BBL-surgery, each animal being used as its own control. 1 H-MRS was performed in the hippocampus (SPECIAL, TE = 2.8 ms) and dMRS in a voxel encompassing the entire brain (DW-STEAM, TE = 15 ms, diffusion time = 120 ms, maximum b-value = 25 ms/μm2) on a 9.4T scanner. The in-vivo MRS acquisitions were further validated with histological measures (immunohistochemistry, Golgi Cox, electron microscopy). The characteristic 1H-MRS pattern of type C HE, i.e. gradual increase of brain glutamine and decrease of main organic osmolytes was observed in the hippocampus of BDL rats. Overall increased metabolite diffusivities (apparent diffusion coefficient and intra-stick diffusivity - Callaghan's model, significant for glutamine, myo-inositol and taurine) and decreased kurtosis coefficients were observed in BDL rats compared to control, highlighting the presence of osmotic stress, and possibly of astrocytic and neuronal alterations. These results were consistent with the microstructure depicted by histology and represented by a decline of dendritic spines density in neurons, a shortening and decreased number of astrocytic processes, and extracellular edema. dMRS enables a non-invasive and longitudinal monitoring of the diffusion behavior of brain metabolites, reflecting in the present study globally-altered brain microstructure in BDL rats, as confirmed ex-vivo by histology. These findings give new insights into metabolic and microstructural abnormalities associated with high brain glutamine and its consequences in type C HE.